2018
DOI: 10.1103/physrevapplied.10.064059
|View full text |Cite
|
Sign up to set email alerts
|

Photocorrosion-Limited Maximum Efficiency of Solar Photoelectrochemical Water Splitting

Abstract: Photoelectrochemical (PEC) water splitting to generate hydrogen is one of the most studied methods for converting solar energy into clean fuel because of its simplicity and potentially low cost. Despite over 40 years of intensive research, PEC water splitting remains in its early stages with stable efficiencies far less than 10%, a benchmark for commercial applications. Here, we revealed that the desired photocorrosion stability sets a limit of 2.48 eV (relative to the normal hydrogen electrode (NHE)) for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 128 publications
1
30
1
Order By: Relevance
“…For comparison, a commercial n-type GaN template has been measured (black squares). The CB edge of GaN is located about 4 eV below the vacuum level; consequently, our results suggest that the CB edge of MBE-grown GZNO layers is located at −3.8 to −5.0 eV relative to the vacuum energy level. , …”
Section: Resultsmentioning
confidence: 56%
“…For comparison, a commercial n-type GaN template has been measured (black squares). The CB edge of GaN is located about 4 eV below the vacuum level; consequently, our results suggest that the CB edge of MBE-grown GZNO layers is located at −3.8 to −5.0 eV relative to the vacuum energy level. , …”
Section: Resultsmentioning
confidence: 56%
“…Therefore, the “holy grail” would be to drive an industrially relevant redox reaction that simultaneously is able to suppress photocorrosion. The thermodynamic criteria toward this reaction (i.e., redox potential) is ultimately limited by (i) the band positions, (ii) the corrosion potentials, and (iii) the bandgap of the perovskite . At this point, it is important to distinguish between photo­(electro)­catalytic or photo­(electro)­synthetic processes. , Light-driven reactions that are thermodynamically “downhill” (Δ G < 0) can be termed photo­(electro)­catalytic, while thermodynamically “uphill” (Δ G < 0) reactions are considered photo­(electro)­synthetic processes.…”
Section: General Considerationsmentioning
confidence: 99%
“…9,10 Thus, photoelectrochemical water splitting (PECWS) is receiving attention as the adaptable solution of the above drawbacks of solar cells since the intermittency, and energy-saving issues can be overcome by converting solar energy to chemical energy, such as green hydrogen. 11 However, the efficiency of PECWS has been known to be about 10%, which is relatively lower than that of the solar cell (over 25%), 12 and the public receptivity and inconvenience in the use of hydrogen gas remain controversial in the usability of PECWS employing the solar-hydrogen energy system. To address these issues, several studies regarding H 2 O 2 generation using PECWS have been reported recently.…”
Section: Introductionmentioning
confidence: 99%